NEW GREEN PROFESSIONS IN BULGARIA IN THE CONTEXT OF TRANSITON TO GREEN ECONOMY - Stoyanova, Zornitsa; Harizanova, Hristina (Economics of Agriculture, 2016)
Transition to green economy sets new requirements and challenges for the types of jobs, skills and knowledge. The paper analyzes and evaluates the importance of categories of green professions by sectors in Bulgaria. The main applied methodical approach for analysis and evaluation of green professions is a system approach. Assessment and analysis of the importance of categories of green professions by sectors is made on the basis of structured interviews with municipal experts from regional government structures involved in the process of implementation of green jobs in the country. According to aggregated and analyzed information are proposed policy recommendations and general conclusions related to implementation of training programs for green employment, use of the best European and world practices for the application of new green professions, improvement of consulting services, changing legal frame work of green jobs, etc.